Pengembangan Keterampilan Profesional Guru Ekonomi melalui Sosialisasi Penyusunan Penelitian Tindakan Kelas di SMK Bistek - Anwar, Syamsul; Hidayati, Syafaatul; Sholeh, Badrus; Alfiansyah, Satria (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity wants to improve teachers' skills in the Preparation of PTK Class Action Research for the Development of Professional Skills of Economics Teachers of Vocational High School BISTEK. This community service activity was carried out directly face-to-face with the attendance of teachers by being given training on the use of classroom action research in an applied manner. Nowadays, the facts found in the dynamics of the world of education are still concerning. One of them is that technological advances are not directly proportional to the progress of teachers' skills. Based on the findings of the lecturer team of the economics education study program at Pamulang University at SMK Bistek, especially economics teachers, around 80% of teachers still use manual references. One of the things that can be done by lecturers of the economic education study program at Pamulang University at SMK Bistek, is through socialization and training assistance to teachers as a form of PKM. The implementation of socialization of the use of reference managers was carried out from 19 to 21 October 2023. The method of approach to solving problems is carried out through the transfer of knowledge. After this community service activity is completed, teachers at SMK Bistek can take advantage of classroom action research so that they can facilitate the preparation of teaching materials. Keywords: Teaching Materials, Teachers; Classroom Action Research